The role of the shear and normal stress gradients on life estimation of notched Al7050-T7451 under multiaxial loadings. (October 2018) - Sá, M.V.C.; Ferreira, J.L.A.; da Silva, C.R.M.; Araújo, J.A.
Highlights: New data under push–pull, torsion and combined axial-torsional loadings for Al 7050-T7451 smooth and notched specimens. Critical distance versus life diagrams in torsion and in push–pull loading conditions. New measure for the critical distance to take into account the effects of normal and shear stress gradients. Lives estimated based on the use of the new equivalent critical distance and the Modified Wöhler Curve Method. Abstract: The aim of this work was to investigate the role of the normal and shear stress gradients on the life estimation of notched Al 7050-T7451 components under multiaxial stress states. In this setting, a new concept of an equivalent critical distance, L eq, was proposed. To validate the analysis a wide number of experimental fatigue data were generated for smooth and notched specimens under push–pull, torsion and combined in phase axial–torsional loadings. From these data, critical distance versus life curves ( L - N f ) were obtained under torsion and push–pull loading conditions. The Modified Wöhler Curve Method (MWCM) critical plane based multiaxial model was used in conjunction with these curves and with the new L eq - N f relationship to estimate lives. The results showed that the L - N f curves obtained from the fully reversed torsion and push–pull tests had opposite behaviours. The best life estimates for the notched specimens under combined in phase axial–torsional loadings were obtained considering the new L eq - N f relationship curve proposed in this work.